EVEKTIFITAS MEDIA PEMBELAJARAN DARING EDMODO DALAM PERKULIAHAN PENDIDIKAN AGAMA ISLAM PADA MASA PANDEMI COVID-19 - AYU LARASATI, MINTEN (Jurnal TAMBORA, 2020)
The Covid-19 outbreak has greatly affected the learning process, because of lecturescannot be implemented in the form of face-to-face lectures. One way to getachieving learning outcomes is to use the system learning mediaonline. Online learning functions as a link between lecturers and studentswith an internet network that can be accessed anytime and anywhere. MediaOnline learning used is Edmodo, a learning platformbased on social networks. The purpose of this research is to analyze the effectiveness of the mediaedmodo in the PAI lecture on semseter 1 students, mix class at the UniversitySumbawa technology. This type of research is a qualitative case study, a methoddata collection used is documentation, interviews and observations.The results of the study concluded that the Covid-19 pandemic changed shapePAI learning becomes online, the media used is edmodo. Edmodo is ratedeffective for carrying out the learning process because, the course material can be accepted,studied and reviewed, assignment collection is simpler, easier and can be scoredaccepted directly, improve student discipline and consistency, easy andnice. Interaction and communication during online learning becomes easier anddirected with the features provided by Edmodo so that the objectives and CPMK PAI canwell earned.